Esophageal foreign bodies under cricopharyngeal level in children: An analysis of 1116 cases - Balci, Akin Eraslan; Eren, Şevval; Eren, Mehmet Nesimi (My University, 2004)
Esophageal foreign bodies (FBs) in children are a commonly seen complaint that can cause severe morbidity. Different methods are used for their extraction. We reviewed our cases and described direct extraction technique. The specifications of 1116 children with esophageal FBs between 1990 and 2000 were evaluated. All FB cases were considered emergencies and intervention was performed in the operating theater. Patients with coins were only sedated and relaxed while the FB was removed under direct vision by McGill forceps. Other FBs were removed under general anesthesia by rigid esophagoscope. There were 1035 coins in 1007 patients and 112 other FBs in 109 children. Mean age was 4.2 years, ranging from 1 month to 15 years. Immediate interventions were performed in 16 (1.4%) patients. Reasons included respiratory distress from pressure in eight (five coins, three toy pieces), increased rupture risk after 4 days in three (all coins) and esophageal rupture in five patients. Four (0.3%) perforations occurred during intervention; two (0.02%, 2/1116) arose from coin extraction, and another two (1.8%, 2/109) were caused by esophagoscopic removal. The success rate for esophagoscopic removal was 95.4% (105/109). Three (0.2%) of 1116 patients underwent surgery to remove FBs. All were esophagoscopy patients, thus the surgery ratio for esophagoscopic removal was 2.7% (3/109). If an FB is diagnosed quickly and removed few problems arise. Esophageal coins can be successfully extracted under direct vision. © 2003 Elsevier B.V. All rights reserved.
Keywords: Children; Esophagus; Foreign body